Diamonds, dispossession & democracy in Botswana - Good, Kenneth (New York James Currey, 2008)
Is Botswana still 'an African miracle'? Thanks to diamonds the country's growth rate was the highest in the world into the 1990s, and regular parliamentary elections judged free on polling day have been held since 1965. However a duopoly of presidentialism and ruling party preponderance has stimulated arrogance, complacency and corruption among the country's rulers. What is 'perpetual democracy'? The ruling BDP is kept in perpetual power by the first-past-the post election system. The President in Botswana is empowered to do whatever he pleases. President Mogae has amended the constitution to ensure the automatic succession of the Vice-President General Ian Khama, the son of Seretse and Ruth Khama.A new Directorate of Intelligence Services provides closer control of power. Why are the Khoisan confined to 'a gulag of special settlements'? The expulsion of the San from Central Kalahari Game Reserve was relentlessly enforced in 1997 and 2002. A multi-cultural coalition asserts that the government is implementing 'a philosophy of cultural genocide on the non-Tswana tribes'. How can the gift of diamonds be turned to reform? Professor Good asserts the need to strengthen and democratise the electoral and voting systems. He sees diversification as essential to reduce the dependency on diamonds. He urges the use of mineral wealth to reduce the gap between rich and poor; half of the population are at present in poverty in a rich country. KENNETH GOOD was Professor of Politics at the University of Botswana when he was expelled from the country. South Africa: Jacana
x, 182 p. : ill., map ; 22 cm.
Keywords: Botswana